2018
DOI: 10.1021/acs.jafc.8b02092
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Proteome Alteration and Functional Modulation of Human Saliva Induced by Dietary Chemosensory Stimuli

Abstract: Saliva flow measurements and SDS-PAGE separation of human whole saliva freshly collected after oral stimulation with citric acid (sour), aspartame (sweet), iso-α-acids (bitter), mono sodium l-glutamate (umami), NaCl (salty), 6-gingerol (pungent), hydroxy-α-sanshool (tingling), and hydroxy-β-sanshool (numbing), followed by tryptic digestion, nano-HPLC-MS/MS, and label-free protein quantitation demonstrated a stimulus- and time-dependent influence of the dietary chemosensates on salivation and the salivary prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 76 publications
0
19
0
3
Order By: Relevance
“…In future studies, it should be tested whether optimized LPO-system-based lozenges in combination with additional agents (such as lysozyme, lactoferrin and fluorides or stimuli of the enzymatic activity by natural products such as 6-gingerol [ 53 ]) are able to improve the showed results.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, it should be tested whether optimized LPO-system-based lozenges in combination with additional agents (such as lysozyme, lactoferrin and fluorides or stimuli of the enzymatic activity by natural products such as 6-gingerol [ 53 ]) are able to improve the showed results.…”
Section: Discussionmentioning
confidence: 99%
“…alleviation of nausea and vomiting [ 26 ]. Pungent 6-gingerol was shown to increase saliva flow in healthy humans by up to 60% [ 17 ]. The excitement observed in dogs chewing the ginger-dipped swab was short-lived; they seemed to react strongly to the first pungent taste and calmed down thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Other substances or methods used were acetic acid, sucrose, sodium chloride, beef-flavored cotton ropes or beef-flavored hydrocellulose swabs [ 11 , 12 , 16 ]. One study in humans, reported the use of ginger with its pungent taste as a salivary stimulant [ 17 ]. So far, to the best of the authors’ knowledge, there have been no studies on using ginger as a salivary stimulant in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Annexin A1 and calgranulin A are upregulated in WMS through an inflammatory-like response after mouth rinsing with bitter, umami and sour tastants (40). Bader et al demonstrated the upregulation of lysozyme in saliva stimulated by citric acid rinse (41). The TRPV1 agonist 6-gingerol upregulated salivary sulfhydryl oxidase 1 resulting in reduced 2-furfurylthiol levels in exhaled breath and thus reduction in the perceived sulphur-like after-smell (42).…”
Section: Introductionmentioning
confidence: 99%